Evidence of Two Oxidative Reaction Steps Initiating Anaerobic Degradation of Resorcinol (1,3-Dihydroxybenzene) by the Denitrifying Bacterium Azoarcus anaerobius - Philipp, Bodo (American Society for Microbiology, 1998)
The denitrifying bacterium Azoarcus anaerobius LuFRes1 grows anaerobically with resorcinol (1,3-dihydroxybenzene) as the sole source of carbon and energy. The anaerobic degradation of this compound was investigated in cell extracts. Resorcinol reductase, the key enzyme for resorcinol catabolism in fermenting bacteria, was not present in this organism. Instead, resorcinol was hydroxylated to hydroxyhydroquinone (HHQ; 1,2,4-trihydroxybenzene) with nitrate or K(3)Fe(CN)(6) as the electron acceptor. HHQ was further oxidized with nitrate to 2-hydroxy-1,4-benzoquinone as identified by high-pressure liquid chromatography, UV/visible light spectroscopy, and mass spectroscopy. Average specific activities were 60 mU mg of protein(−1) for resorcinol hydroxylation and 150 mU mg of protein(−1) for HHQ dehydrogenation. Both activities were found nearly exclusively in the membrane fraction and were only barely detectable in extracts of cells grown with benzoate, indicating that both reactions were specific for resorcinol degradation. These findings suggest a new strategy of anaerobic degradation of aromatic compounds involving oxidative steps for destabilization of the aromatic ring, different from the reductive dearomatization mechanisms described so far.